2009
DOI: 10.1021/pr9004103
|View full text |Cite
|
Sign up to set email alerts
|

Human Urinary Metabolomic Profile of PPARα Induced Fatty Acid β-Oxidation

Abstract: Activation of the peroxisome proliferator-activated receptor α (PPARα) is associated with increased fatty acid catabolism and is commonly targeted for the treatment of hyperlipidemia. To identify latent, endogenous biomarkers of PPARα activation and hence increased fatty acid β-oxidation, healthy human volunteers were given fenofibrate orally for 2 weeks and their urine profiled by UPLC-QTOFMS. Biomarkers identified by the machine learning algorithm random forests included significant depletion by day 14 of bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 28 publications
1
46
1
Order By: Relevance
“…Studies in healthy volunteers have shown that PPAR-a activation increases urinary uric acid excretion (32). In accordance, fenofibrate (a PPAR-a activator) lowers serum uric acid levels (33).…”
Section: Discussionmentioning
confidence: 92%
“…Studies in healthy volunteers have shown that PPAR-a activation increases urinary uric acid excretion (32). In accordance, fenofibrate (a PPAR-a activator) lowers serum uric acid levels (33).…”
Section: Discussionmentioning
confidence: 92%
“…In addition, PPAR-α activation upregulates gene expression of FA2H , CPT , and ACAD8 (Rakhshandehroo et al ., 2007; Makowski et al ., 2009; Takeda et al ., 2013), findings that may explain the associations found between 2-hydroxypalmitate, glutarylcarnitine [reductions in glutarylcarnitine are related to levels of CPT (Lee & Wolfgang, 2012)], and isobutyrylcarnitine with physical function. Separately, PPAR-α activation has been shown to reduce urinary excretion of isobutyrylcarnitine (Patterson et al ., 2009) and cinnamoylglycine (Zhen et al ., 2007), and cinnamoylglycine is increased in PPAR −/− mice (Zhen et al ., 2007). Collectively, these data suggest a role for mechanisms related to PPAR-α activation on influencing physical function in functionally-limited older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolomics has revealed the downregulated tryptophan-nicotinamide pathways following Wy-14,643 treatment ( 9 ) and the decreased excretion of carnitine-conjugated metabolites by fenofi brate treatment in humans ( 13 ). Furthermore, an increase in the excretion of glycine conjugated metabolites was observed in Ppara -null mice ( 9 ), and the long-chain fatty acid carnitines, including palmitoylcaritine, myristolcarnitine, oleoylcarnitine, and palmitoleoylcarnitine, were elevated in the serum after suppression of PPAR␣ signal transduction by acetaminophen ( 14 ).…”
Section: Identifi Cation and Quantitation Of Urinary And Serum Metabomentioning
confidence: 99%